usun niewymierność z mienownika
a) 4
---------
√5 + 2
b) 2
---------
3 - √7
c) 3
---------
5 + 2 √5
d) 10
-------------
3√2 - 4
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
a)![\frac{4}{\sqrt{5}+2} = \frac{4}{\sqrt{5}+2} \cdot \frac{\sqrt{5}-2}{\sqrt{5}-2} = \frac{4(\sqrt{5}-2)}{(\sqrt{5}+2)(\sqrt{5}-2)} = \frac{4\sqrt{5}-8}{5-4} = 4\sqrt{5}-8 \frac{4}{\sqrt{5}+2} = \frac{4}{\sqrt{5}+2} \cdot \frac{\sqrt{5}-2}{\sqrt{5}-2} = \frac{4(\sqrt{5}-2)}{(\sqrt{5}+2)(\sqrt{5}-2)} = \frac{4\sqrt{5}-8}{5-4} = 4\sqrt{5}-8](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B%5Csqrt%7B5%7D%2B2%7D+%3D+%5Cfrac%7B4%7D%7B%5Csqrt%7B5%7D%2B2%7D+%5Ccdot+%5Cfrac%7B%5Csqrt%7B5%7D-2%7D%7B%5Csqrt%7B5%7D-2%7D+%3D+%5Cfrac%7B4%28%5Csqrt%7B5%7D-2%29%7D%7B%28%5Csqrt%7B5%7D%2B2%29%28%5Csqrt%7B5%7D-2%29%7D+%3D+%5Cfrac%7B4%5Csqrt%7B5%7D-8%7D%7B5-4%7D+%3D+4%5Csqrt%7B5%7D-8)
b)![\frac{2}{3-\sqrt{7}} = \frac{2}{3-\sqrt{7}} \cdot \frac{3+\sqrt{7}}{3+\sqrt{7}} = \frac{2(3+\sqrt{7})}{(3-\sqrt{7})(3+\sqrt{7})} = \frac{2(3+\sqrt{7})}{9-7} = \frac{2(3+\sqrt{7})}{2} = 3+\sqrt{7} \frac{2}{3-\sqrt{7}} = \frac{2}{3-\sqrt{7}} \cdot \frac{3+\sqrt{7}}{3+\sqrt{7}} = \frac{2(3+\sqrt{7})}{(3-\sqrt{7})(3+\sqrt{7})} = \frac{2(3+\sqrt{7})}{9-7} = \frac{2(3+\sqrt{7})}{2} = 3+\sqrt{7}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3-%5Csqrt%7B7%7D%7D+%3D+%5Cfrac%7B2%7D%7B3-%5Csqrt%7B7%7D%7D+%5Ccdot+%5Cfrac%7B3%2B%5Csqrt%7B7%7D%7D%7B3%2B%5Csqrt%7B7%7D%7D+%3D+%5Cfrac%7B2%283%2B%5Csqrt%7B7%7D%29%7D%7B%283-%5Csqrt%7B7%7D%29%283%2B%5Csqrt%7B7%7D%29%7D+%3D+%5Cfrac%7B2%283%2B%5Csqrt%7B7%7D%29%7D%7B9-7%7D+%3D+%5Cfrac%7B2%283%2B%5Csqrt%7B7%7D%29%7D%7B2%7D+%3D+3%2B%5Csqrt%7B7%7D+)
c)![\frac{3}{5+2\sqrt{5}} = \frac{3}{5+2\sqrt{5}}} \cdot \frac{5-2\sqrt{5}}{5-2\sqrt{5}} = \frac{3(5-2\sqrt{5})}{(5+2\sqrt{5})(5-2\sqrt{5})} = \frac{3(5-2\sqrt{5})}{25- 4 \cdot 5} = \frac{15-6\sqrt{5}}{25- 20} = \frac{15-6\sqrt{5}}{5} \frac{3}{5+2\sqrt{5}} = \frac{3}{5+2\sqrt{5}}} \cdot \frac{5-2\sqrt{5}}{5-2\sqrt{5}} = \frac{3(5-2\sqrt{5})}{(5+2\sqrt{5})(5-2\sqrt{5})} = \frac{3(5-2\sqrt{5})}{25- 4 \cdot 5} = \frac{15-6\sqrt{5}}{25- 20} = \frac{15-6\sqrt{5}}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B5%2B2%5Csqrt%7B5%7D%7D+%3D+%5Cfrac%7B3%7D%7B5%2B2%5Csqrt%7B5%7D%7D%7D+%5Ccdot+%5Cfrac%7B5-2%5Csqrt%7B5%7D%7D%7B5-2%5Csqrt%7B5%7D%7D+%3D+%5Cfrac%7B3%285-2%5Csqrt%7B5%7D%29%7D%7B%285%2B2%5Csqrt%7B5%7D%29%285-2%5Csqrt%7B5%7D%29%7D+%3D+%5Cfrac%7B3%285-2%5Csqrt%7B5%7D%29%7D%7B25-+4+%5Ccdot+5%7D+%3D+%5Cfrac%7B15-6%5Csqrt%7B5%7D%7D%7B25-+20%7D+%3D+%5Cfrac%7B15-6%5Csqrt%7B5%7D%7D%7B5%7D+)
d)
![= \frac{10(3\sqrt{2}+4)}{2} = 5(3\sqrt{2}+4) = 15\sqrt{2} + 20 = \frac{10(3\sqrt{2}+4)}{2} = 5(3\sqrt{2}+4) = 15\sqrt{2} + 20](https://tex.z-dn.net/?f=%3D+%5Cfrac%7B10%283%5Csqrt%7B2%7D%2B4%29%7D%7B2%7D+%3D+5%283%5Csqrt%7B2%7D%2B4%29+%3D+15%5Csqrt%7B2%7D+%2B+20)